Cyber insecurity navigating the perils of the next information age - Harrison, Richard M. 1981-; Herr, Trey (Rowman & Littlefield Publishers, 2016)
Growing dependence on cyberspace for commerce, communication, governance, and military operations has left society vulnerable to a multitude of security threats. Mitigating the inherent risks associated with the use of cyberspace poses a series of thorny public policy problems. In this volume, academics, practitioners from both private sector and government, along with former service members come together to highlight sixteen of the most pressing contemporary challenges in cybersecurity, and to offer recommendations for the future. As internet connectivity continues to spread, this book will offer readers greater awareness of the threats of tomorrow--and serve to inform public debate into the next information age.